STUDI IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN IPS DI SMPN 1 INDRALAYA - Riski Utami Putriani; Riswan Jaenudin; Dewi Koryati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
This study entitled Implementation Study of Curriculum 2013 on IPS Subjects at SMPN 1 Indralaya. The formulation is how the level of ability of IPS subject teachers in implementing the 2013 curriculum on the aspects of planning, process, and assessment of learning. As for the purpose of this study is to determine the level of ability of IPS subject teachers in implementing the 2013 curriculum on aspects of process planning, and assessment of learning. In this study, the subject of research is the subject teachers IPS SMPN 1 lndralaya teaching in class VII amounted to 2 people. The data pengmnpulan techniques used in this study are observation, interviews, and documentation. Statistics used in analyzing data is the mean formula while to test the validity of data using triangulation data. From the results of data analysis conducted then the level of ability of teachers subjectsIPS at SMPN 1 India in mengimplememntasikan 2013 curriculum on the aspect of planning included in the integori capable enough with a percentage of 50%, then on aspects of the learning process included in the category very capable with percentage of 88.15 %, and on the aspect of the assessment of learning included in the category of capable enough with the percentage appears at 64.28% and not visible 35.7%. Although the actual 2013 curriculum is not fully applicable by teachers in learning activities this is due to the lack of facilities and infrastructure as well as instructional media to support the implementation of the 2013 curriculum at SMPN 1 Indralaya. However, the implementation of the 2013 curriculum in these social studies subjects can still be continued for the learning process.